WAYS OF DEVELOPING PROPERTIES OF THE AGRICULTURAL PROPERTY AGENCY (ON THE EXAMPLE OF KUJAWSKO-POMORSKI REGION) - Smytry, Grzegorz; Wawrzyniak, Bogdan (Acta Scientiarum Polonorum. Oeconomia, 2003)
The Agency of Agricultural Property of The State Treasury was formed to develop lands of state farms and National Found of Land. The Agency started its activity in 1992 and in the middle of 2003 was converted into The Agency of Agricultural Property. The research was carried in a ground of one local branch of the Agricultural Property Agency. The results of the research are shown in three groups: 1. as a sale of the land; 2. as a lease of the land; 3. other ways of property developed. The analysis was made in three regions (till 1998) and after emerging of one province in a scale of the whole kujawsko-pomorski region.